Clínica da Palavra: a poética do encontro na produção da vida - Salgado, Guilherme Ávila (Universidade Federal de São Carlos, 2018)
Itinerância Poética is a movement that seeks to promote encounters based on poetry. It happens through the komboteca that harbors a collection with more than a thousand books that, for the most part, are of independent production. Poetic Roaming traveled about 12,000 km, from Minas Gerais to Maranhão, through thewilderness, and from Maranhão to Minas Gerais, by the coast, with the main objective of occupying public spaces with public actions, strengthening local movements that already exist.This research presents, through the auto-ethnographic method, the importance of access to art for anyone who wants (to be able to produce it and / or to access it), the production of poetry (capacity to create and produce interventions in the world) and popular culture (the place of the common in the production of life, in the daily life) as determinants and conditioning factors to the health of individual and collective subjects, indispensable to the life. The proposal of this study challenges the place of the traditional clinic inviting the lector to think in broader perspectives, beyond the health-disease binomial, that is often understood as antagonistic states. It allows reinventing the concept of clinic asa space of engagement and co-responsibility with human suffering, through the construction of life possibilities and in the production of new subjectivities.
Clinic of the Word: the poetics of the encounter in the production of life
Keywords: Clínica da palavra; Poesia; Saúde; Clinic of the word; Poetry; Health; CIENCIAS DA SAUDE::SAUDE COLETIVA